Amitraz induced cytotoxic effect on bovine cumulus cells and impaired oocyte maturation - Nikoloff, Noelia (2021)
The aim of this study was to evaluate the genotoxic and cytotoxic effects of amitraz (AMZ) on the primary culture of bovine cumulus cells (CC) and oocyte nuclear maturation. Cytotoxicity was evaluated by assessing mitochondrial activity with the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. Genotoxicity was estimated using the alkaline single cell gel electrophoresis (SCGE) assay. Apoptosis was detected with the Annexin V-affinity assay. The in vitro maturation test was performed in bovine oocytes. To understand AMZ action, glutathione content, superoxide dismutase enzyme activity, and lipid peroxidation were evaluated in CC. Results showed that AMZ lethal concentration (LC 5024h) for bovine CC was 32.55 μg/mL (MTT assay). A 25 μg/mL induced late apoptosis and necrotic cells (p < 0.05); however, DNA damage was decreased at the same concentration (SCGE assay; p < 0.05). A decrease in metaphase II was observed at 25 μg/mL, and degenerate oocytes were observed at 15 and 25 μg/mL (p < 0.05). None of the oxidative stress parameters evaluated showed significant differences. This study contributes to a better understanding of AMZ in this model, suggesting its potential cytotoxicity and impact on bovine reproduction.